2014
DOI: 10.1007/s13105-014-0323-6
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous date fruit extract protects against lipid peroxidation and improves antioxidant status in the liver of rats subchronically exposed to trichloroacetic acid

Abstract: Trichloroacetic acid (TCA) is a prominent by-product of the chlorination of drinking water. It induces cell damage by producing free radicals and reactive oxygen species. The present study was carried out to evaluate the potential hepatoprotective role of the aqueous date extract (ADE) against TCA-induced liver injury. Forty-eight male Wistar rats were randomly divided into six groups of eight: group I served as the control; group II was given ADE by gavage; groups III and IV received TCA as drinking water at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
3
16
0
1
Order By: Relevance
“…The present study showed that TCA induced a significant increase in the activity of SOD, CAT, and GPx compared with normal CG; these results are agreement with El Arem et al; Hassoun and Cearfoss [52,53], who confirmed the increase in these enzymes activity in the serum when animals treated with TCA. TCA treatment resulted in an increase in SOD and CAT activities suggesting a partial role of SOD-CAT in protection against cellular toxicity and the contribution of superoxide anion and H 2 O 2 to the previously observed oxidative cellular damage associated with TCA treatment [53].…”
Section: Abozid and Faridsupporting
confidence: 93%
“…The present study showed that TCA induced a significant increase in the activity of SOD, CAT, and GPx compared with normal CG; these results are agreement with El Arem et al; Hassoun and Cearfoss [52,53], who confirmed the increase in these enzymes activity in the serum when animals treated with TCA. TCA treatment resulted in an increase in SOD and CAT activities suggesting a partial role of SOD-CAT in protection against cellular toxicity and the contribution of superoxide anion and H 2 O 2 to the previously observed oxidative cellular damage associated with TCA treatment [53].…”
Section: Abozid and Faridsupporting
confidence: 93%
“…Previous studies reported similar findings for palm date extracts. For instance, in a rat model of trichloroacetic acid (TCA)-induced hepatoxicity, El Arem et al [16] demonstrated that aqueous palm fruit extract attenuated enhanced redox state in liver as evidenced by significant reduction in hepatic lipid peroxidation products (MDA) with improvement of antioxidant enzyme e.g. catalase, SOD and glutathione peroxidase activities.…”
Section: Nc Group (N=10) Dm Group (N=4) Dm+afe Group (N=8) Dm+mfe Gromentioning
confidence: 99%
“…The extracts of palm date fruits and seeds showed strong antioxidant properties in many in vitro studies [9,13] and in vivo studies [10,14,15]. Recently, El Arem et al [16] demonstrated the beneficial effect of aqueous palm fruit extract (ADE) against the oxidative stress and hepatotoxicity induced by trichloroacetic acid (TCA) and Saafi-Ben Salah et al [17] and El Arem et al [18] demonstrated the beneficial effect for palm date extracts against nephrotoxicity induced by dichloroacetic acid and dimethoate respectively. Moreover, we demonstrated in a recent study by our group that palm date extracts ameliorates the hepatic dysfunctions in type 2 DM [19].…”
Section: Introductionmentioning
confidence: 99%
“…OFD is rich in polyphenolic substances, which have received widespread attention because of their potential for preventing some common chronic diseases. Polyphenols are reported to have antiinflammatory, antioxidant, antidiabetic, and hepatoprotective effects (Bashandy et al 2014;El Arem et al 2014).…”
Section: Discussionmentioning
confidence: 99%